Effect of Golden Dock (Rumex maritimus) Residues on Weed Growth Performance of Boro Rice (cv. BRRI dhan58 and BRRI dhan74) - Md. Liton Mia; Sarwar Islam; Farhana Sultana Farha; Md. Kamrul Hasan; Md. Abdur Rahim Sium; Md. Tutul Hossen; Farhana Zaman; Md. Abdus Salam; Md. Shafiqul Islam (AgroEnvironmental Sustainability)
Allelopathy plays an important role in weed control and crop productivity. We evaluated the effect of the residues of Rumex maritimus on the growth performance of boro rice comprising two cultivars i.e., BRRI dhan58 and BRRI dhan74 and four rates of R. maritimus residues treatment such as 0, 1.0, 2.0, 3.0 t/ha and a farmers practice. The experiment was laid out in a randomized complete block design (RCBD) with three replications. We identified four weed species (Panikachu, Shama, Shusni, Chesra) belonging to four families. Dry weight of Shama, Shusni, Chesra except Panikachu were significantly affected by variety. The highest Shama dry weight (6.61 g/0.0625 m2) was found in BRRI dhan74 and the lowest weed population (5.81 g/0.0625 m2) was obtained in BRRI dhan58 at 1% level of probability and also the highest Chesra dry weight (5.58 g/0.0625 m2) was found in BRRI dhan74 and the lowest weed population (4.89g/0.0625 m2) was obtained in BRRI dhan58 at 1% level of probability. The highest Shusni dry weight (5.11 g/0.0625 m2) was found in BRRI dhan58 and the lowest weed population (5.00 g/0.0625 m2) was obtained in BRRI dhan74 at a 1% level of probability. Weed density and dry weight were also significantly affected by variety and residue treatment. Results of this study indicate that R. maritimus residues showed the potential to inhibit weed growth of boro rice. Therefore, R. maritimus residues might be used as an alternative way for weed management in effective and sustainable crop production.